1996
DOI: 10.3354/meps142121
|View full text |Cite
|
Sign up to set email alerts
|

Filtration and resuspension of particulate matter and phytoplankton on an intertidal mussel bed in the Oosterschelde estuary (SW Netherlands)

Abstract: In situ measurements were carried out on an intertidal mussel bed in the Oosterschelde estuary, SW Netherlands. Exchange of suspended particulate matter and phytoplankton between the water column and the mussel bed was measured with a Benthic Ecosystem Tunnel. In situ clearance rates of the mussel bed were compared to clearance rates of individual mussels measured in a field station under amblent conditions. Concentrations of suspended particulate matter (SPM) and particulate organic carbon (POC) in the water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 41 publications
2
34
1
Order By: Relevance
“…Prins et al (1996) found that clearance rates measured in situ in the Oosterschelde estuary were reasonably similar to laboratory measurements. In our experiments, seston concentration and composition were in the same range in the laboratory and the field situation (Table 1).…”
Section: Discussionmentioning
confidence: 54%
“…Prins et al (1996) found that clearance rates measured in situ in the Oosterschelde estuary were reasonably similar to laboratory measurements. In our experiments, seston concentration and composition were in the same range in the laboratory and the field situation (Table 1).…”
Section: Discussionmentioning
confidence: 54%
“…The processing of suspended materials in the water column carried out by suspension filter feeders was significant in assessing trophic relationships in freshwater, estuarine and marine ecosystems (Prins 1996, Espinosa 2008, Manganaro 2009, Sarikhani & Javanshir 2010, Mamun & Khan 2011. This study suggested that natural population of in Loay-Loboc River was resilient in their environment, which agreed to experiments conducted by Yap and Mohd Azri (2009) and by Bayen .…”
Section: Methodsmentioning
confidence: 99%
“…Several rivers ( Fig. 1: Elbe, Weser, Ems, and Rhine through the Ijsselmeer) discharge into the German Bight supplying it with high nutrient loads (Beddig et al, 1997;Radach, 1992). Especially in the estuaries in the east, waters are highly turbid due to riverine suspended particulate matter.…”
Section: Study Areamentioning
confidence: 99%
“…It also decreases light availability for phytoplankton by increasing turbidity, which is suggested to be pivotal for phytoplankton bloom control (Townsend et al, 1994). In shallow coastal environments, vertical mixing may even raise phytoplankton mortality because of grazing by benthic filterfeeders (Cloern, 1996;Prins et al, 1996). In contrast, freshwater inputs from rivers may lead to a haline stratification in Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%